Growth, Yield and Profitability of Cabbage (Brassica oleracea L.) as Influenced by Applied Nitrogen and Plant Spacing - Haque, Firoj Asadul; Islam, N; Islam, Md Nazrul; Ullah, Ahsan; Sarkar, Md Dulal (The Agriculturists, 2016)
An experiment was conducted with cabbage during October 2012 to February 2013 at the Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh. Four levels of nitrogen: viz. 0, 150, 250 and 350 kg ha-1 and three plant spacings: 50 x 30, 50 x 40 and 50 x 50 cm were applied in a Randomized Complete Block Design with three replications. Nitrogen @ 250 kg ha-1 with the spacing of 50 x 50 cm was more effective and produced the highest fresh weight of head(2.17 kg), marketable head yield (86.93 t ha-1). This treatment was also more profitable than the rest of the treatments, while the lowest profit was in N0S1. The Agriculturists 2015; 13(1) 35-45